Degradation processes in encapsulated ZnS: Cu powder electroluminescent phosphors - Popovych, K.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
In this paper we present experimental results of the studying degradation processes in electroluminescent panels, prepared from encapsulated ZnS:Cu powder phosphors and theoretical simulation of energy parameters for the phosphor. Energy band diagrams ZnS, Cu₂S, ZnS-Cu₂₋xS heterojunction and Cu-ZnS metal-semiconductor junction have been constructed and cohesive energies for Zn-S, Cu-S, Zn-O, Cu-O and Zn-Cu bonds have been calculated by the method based on a linear combination of atomic orbitals and pseudo-potential. Time dependences of brightness have been found to adequately fit a two-component exponential dependence. The first part of the exponential curve has been attributed to the diffusion processes taking place in Cu₂₋xS, and the second one to the diffusion of Cu in ZnS matrix.